The no-tillage system and cover crops-Alternatives to increase upland rice yields - Nascente, Adriano Stephan; Crusciol, Carlos Alexandre Costa [UNESP]; Cobucci, Tarcísio (Elsevier, 2013)
Upland rice (Oryza sativa L.) cultivation has been increasing in importance in Asia while water availability for irrigation has been decreasing because of rapid growth in industry and urban centers. Therefore, the development of technologies that increase upland rice yields under aerobic conditions, thereby saving water, would be an effective strategy to avoid a decrease in global rice grain production. The use of the no-tillage system (NTS) and cover crops that maintain soil moisture would prove advantageous in the move toward sustainable agriculture. However, upland rice develops better in plowed soil, and it has been reported that this crop does not perform well under the NTS. Therefore, the aim of this study was to investigate the effect of cover crops on upland rice grain yield and yield components sowed in a NTS. A field experiment was conducted during two growing seasons (2008-2009 and 2009-2010), and treatments consisted of growing rice under five cover crops in a NTS and two control treatments under the conventional tillage system (plowing once and disking twice). Treatments were carried out in a randomized block design with three replications. Our findings are as follows: On average, Brachiaria brizantha (12.32Mgha-1), Brachiaria ruziziensis (11.08Mgha-1) and Panicum maximum (11.62Mgha-1) had outstanding biomass production; however, these grasses provided the worst upland rice yields (2.30, 2.04, and 2.67Mgha-1, respectively) and are not recommended as cover crops before upland rice. Millet and fallow exhibited the fastest straw degradation (half-lives of 52 and 54 days, respectively), and millet exhibited the fastest nitrogen release (N half-life of 28 days). The use of a NTS was promising when millet was used as a cover crop; this allowed the highest upland rice yield (3.94Mgha-1) and did not statistically differ from plowed fallow (3.52Mgha-1). © 2012 Elsevier B.V.
Keywords: Cover crops; Crop-livestock integration; Soil management; Sustainable agriculture; agronomy; alternative agriculture; cover crop; crop production; crop yield; grass; growing season; irrigation system; millet; mixed farming; oxic conditions; plowing; rice; soil management; soil moisture; straw; technological development; upland region; water availability; zero tillage; Asia; Brachiaria; Oryza sativa; Panicum; Panicum maximum; Poaceae; Urochloa brizantha